Seroprevalence of Bordetella pertussis Infection in Patients With Chronic Obstructive Pulmonary Disease in England: Analysis of the AERIS Cohort. (1st July 2021) - Wilkinson, Tom M. A.; Van den Steen, Peter; Cheuvart, Brigitte; Baudson, Nathalie; Dodet, Monique; Turriani, Elisa; Harrington, Lauriane; Meyer, Nadia; Rondini, Simona; Taddei, Laura; Mukherjee, Piyali
Abstract: Pertussis is underdiagnosed and underreported in adults and patients with underlying conditions. Patients with chronic obstructive pulmonary disease (COPD) may be at increased risk of severe pertussis. Understanding the true prevalence of pertussis infections in such patients is important. We therefore evaluated the seroprevalence of anti-pertussis toxin (PT) antibodies in a cohort of 40–85-year-old patients diagnosed with moderate, severe or very severe COPD enrolled (between June 2011 and June 2012) in the prospective, observational "Acute Exacerbation and Respiratory InfectionS in COPD" (AERIS; NCT01360398) study, conducted in England. Serum anti-PT antibodies were measured in 104 patients using an enzyme-linked immunosorbent assay on samples collected 12 months (M12) and 24 months (M24) after enrollment. Overall, 14/104 (13.5%) patients had anti-PT concentrations ≥50 IU/mL at M12 or M24, indicative of exposure to Bordetella pertussis during the preceding 2–3 years. Of these, 6/104 (5.8%) had anti-PT ≥70 IU/mL, of whom 3/104 (2.9%) had anti-PT ≥120 IU/mL, indicative of exposure within 12 and 6 months, respectively. These results show a high circulation of B. pertussis in 40–85-year-old patients with moderate, severe or very severe COPD in England between 2012 and 2014, and call for enhanced immunization to prevent pertussis infections in such patients.